Managing Conflicts in Relational Contracts - Li, Jin; Matouschek, Niko (American Economic Review, 2013)
A manager and a worker are in an infinitely repeated relationship in which the manager privately observes her opportunity costs of paying the worker. We show that the optimal relational contract generates periodic conflicts during which effort and expected profits decline gradually but recover instantaneously. To manage a conflict, the manager uses a combination of informal promises and formal commitments that evolves with the duration of the conflict. Finally, we show that liquidity constraints limit the manager's ability to manage conflicts but may also induce the worker to respond to a conflict by providing more effort rather than less. (JEL C73, D74, D86, J33, J41, M12)